Gambaran Resiliensi Akademik Mahasiswa Kelas Internasional dan Implikasinya dalam Pelayanan Konseling - Aullya, Dhita Putri; Nurfarhanah, Nurfarhanah (YASIN, 2024)
This research is motivated by the number of students who have low academic resilience, this is caused by students not believing in their abilities, not being able to control themselves etc. The purpose of this study is to describe: 1) academic resilience of international class students, 2) academic resilience of international class students in terms of confidence (self belief), 3) academic resilience of international class students in terms of control (a sense of control), 4) academic resilience of international class students in terms of composure (anxiety), 5) academic resilience of international class students in terms of commitment (persistence). This research uses quantitative methods with a descriptive approach. The research sample was 72 international class students of the Guidance and Counseling Department of Padang State University who were selected using the total sampling technique. Data obtained by giving a research questionnaire in the form of an academic resilience instrument with a Likert scale model to students who have been tested for validity and data processing using descriptive statistical methods. The results showed that the academic resilience of international class students of BK UNP was generally in the high category with a percentage of (47%).